Efektivitas Media Pembelajaran Cabri 3D Berbasis TPACK Pada Model Problem Based Learning (PBL) Terhadap Kemampuan Pemahaman Konsep Geometri Siswa - Sopiyaturrohmah, Siti; Yuliardi, Ricki (Papanda, 2025)
Mathematics is a field of study that requires students to continuously develop a deep understanding of concepts, thereby enhancing their conceptual comprehension skills. This study aims to examine and measure the effectiveness of the TPACK-based Cabri 3D learning media integrated into the Problem-Based Learning (PBL) model in improving students’ understanding of geometric concepts at SMK Negeri 1 Kuningan. The sampling technique employed was purposive sampling, where from the population of the Light Vehicle Engineering (Automotive) Department, class XI TKRO 1 was selected as the experimental group and class XI TKRO 3 as the control group. This research utilized an experimental method with a nonequivalent control group design. Prior to testing the hypothesis regarding differences in conceptual understanding improvement between the experimental and control classes, normality and homogeneity tests were conducted on the N-gain scores of each class. The normality test using the Shapiro-Wilk method indicated that the data were normally distributed, while the homogeneity test showed that the data were not homogeneous. Consequently, as the assumptions for a parametric test were not met, hypothesis testing was carried out using the nonparametric Mann-Whitney U test. The results revealed that the calculated t-value exceeded the critical t-table value, leading to the rejection of H₀, which indicates a significant difference in students’ conceptual understanding between the experimental and control groups. This finding suggests that the TPACK-based Cabri 3D learning media is effective in enhancing students’ conceptual understanding. Moreover, the questionnaire results showed positive student responses, indicating that the use of such learning media also fosters greater student engagement in the learning process.